2020
DOI: 10.1093/aesa/saz065
|View full text |Cite
|
Sign up to set email alerts
|

CLIMEX and MED-FOES Models for Predicting the Variability in Growth Potential and Persistence of Mediterranean Fruit Fly (Diptera: Tephritidae) Populations

Abstract: CLIMEX and MED-FOES models integrate climate and data on Mediterranean fruit fly (medfly), Ceratitis capitata (Wiedemann), biology and use it to define the environmental suitability for the pest at specific geographical locations. CLIMEX calculates growth indices as indicators of conditions that are suitable for medfly population growth. MED-FOES incorporates additional information on pest management interventions to simulate the process and timing of medfly eradication. CLIMEX simulations of climatic suitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Climate change poses new risks of alien pest insect invasion and expansion into territories [47]. Furthermore, insecticide resistance is becoming a serious problem al C. capitata [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Climate change poses new risks of alien pest insect invasion and expansion into territories [47]. Furthermore, insecticide resistance is becoming a serious problem al C. capitata [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have predicted the PGD of the MFF by using the CLIMEX model [ 24 , 26 ], which lists MFF parameters as an example [ 27 ]. However, these predictions did not encompass all documented distributions of MFF, most likely because records of the known occurrence of this species have been recently updated.…”
Section: Methodsmentioning
confidence: 99%
“…Local climate at the destination of incursions is another key component of risk ( Stephens et al 2016 ), including the effects of artificial irrigation (e.g., Szyniszewska et al 2020 ). In Australia, modeling has identified that the optimal climatic niche for B. tryoni is moving south, primarily along the coast ( Sultana et al 2017 , Simpson et al 2020 ).…”
Section: Target Species and Risk Assessmentmentioning
confidence: 99%
“…Similarly, trapping is conducted year-round in southern California, except in Imperial County and Coachella Valley in the height of summer ( Gilbert et al 2013 ). Further north in California, winter cold limits fruit fly persistence ( De Villiers et al 2016 , Szyniszewska et al 2020 ). In the San Francisco Bay area, trimedlure, methyl eugenol, and torula yeast traps are deployed from April to November, while cuelure traps are set out from June through October.…”
Section: Seasonal Trap Deploymentmentioning
confidence: 99%